Using fire cupping therapy to enhance early lactation to prevent stunting in coastal regions - Herman, Herman; Uksim, Muhammad; Layuk, Yobel Patrisia; Rahayu, Sri; Jumatrin, Nur Fitriah; Nurlin, Nurlin (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2024)
Globally, stunting continues to be a serious public health problem. Efforts to prevent stunting include exclusive breastfeeding and complementary feeding. The success of early breastfeeding after childbirth determines the success of exclusive breastfeeding, which contributes to reducing the stunting prevalence. Breast pain and insufficient milk production are causes of early breastfeeding failure. Fire cupping therapy can be an alternative to overcome these problems. Unfortunately, research on the effect of this therapy on early breastfeeding initiation is limited. This study aims to determine the effect of fire cupping therapy on early lactation in postpartum women in the coastal area of Konawe Regency. A quasi-experimental design with a pre-test and post-test nonequivalent control group was used in this study. Purposive sampling was used to select samples, and 30 respondents were obtained (divided into intervention and control groups of 15 respondents each). The intervention group received fire cupping therapy 2 times for 30 minutes. Univariate analysis using descriptive analysis and bivariate analysis using paired t-test. In the intervention group there was a significant increase in the mean LATCH score of 1.26 (p-value <0.05). In the control group, the mean LATCH score of 0.67 was not significant (p-value > 0.05). Fire cupping therapy effectively improves early lactation outcomes in postpartum mothers. Incorporating complementary therapies into maternal health care procedures may improve breastfeeding outcomes and general maternal and newborn health, especially for stunting prevention. Future studies should investigate the long-term impact of fire cupping therapy on breastfeeding outcomes and involve larger and more varied populations.